Developing a VR Map for the Faculty of Computer Science, Ubon Ratchathani Rajabhat University: A Design Science Approach - Srisawatsakul, Charnsak; Boontarig, Waransanang; Kitpermkiad, Santanee; Chotiphan, Tanarat; Chotiphan, Theerada (Journal of Applied Informatics and Technology, 2024)
This research aims to develop a virtual reality (VR) map for the Faculty of Computer Science at Ubon Ratchathani Rajabhat University and evaluate the satisfaction level of its users. This study used a design science research approach to address real-world issues such as navigating and exploring a university faculty, which can be difficult for new students and visitors. This study’s artifact is a working prototype of a VR map of the Faculty of Computer Science building, which was evaluated with 115 student participants using a quantitative questionnaire. The results showed that the VR map received a high level of satisfaction, with a mean score of 4.30 for the overall experience. The users particularly appreciated the system’s ease of use, convenience, and readability of the text and images displayed. However, some users suggested improvements such as clearer room signs, more detailed point of interest (POI) information, and the inclusion of multimedia elements such as videos and narrations. The findings of this study can help with the design and development of virtual reality maps for university campuses, as well as future research in this field.